Microscopic Modeling of País Grape Seed Extract Absorption in the Small Intestine - Morales, Cristian (Springer US, 2013)
The concentration profiles and the absorbed fraction (F) of the País grape seed extract in the human small intestine were obtained using a microscopic model simulation that accounts for the extracts' dissolution and absorption. To apply this model, the physical and chemical parameters of the grape seed extract solubility (C(s)), density (ρ), global mass transfer coefficient between the intestinal and blood content (k) (effective permeability), and diffusion coefficient (D) were experimentally evaluated. The diffusion coefficient (D = 3.45 × 10(−6) ± 5 × 10(−8) cm(2)/s) was approximately on the same order of magnitude as the coefficients of the relevant constituents. These results were chemically validated to discover that only the compounds with low molecular weights diffused across the membrane (mainly the (+)-catechin and (−)-epicatechin compounds). The model demonstrated that for the País grape seed extract, the dissolution process would proceed at a faster rate than the convective process. In addition, the absorbed fraction was elevated (F = 85.3%). The global mass transfer coefficient (k = 1.53 × 10(−4) ± 5 × 10(−6) cm/s) was a critical parameter in the absorption process, and minor changes drastically modified the prediction of the extract absorption. The simulation and experimental results show that the grape seed extract possesses the qualities of a potential phytodrug.